Profilscience Motivation dalam Kurikulum Berbasis Pondok Pesantren: Studi Kasus di MTS Muhammadiyah Al Manar Demak - Dewi, Nila Sari; Hayat, Muhammad Syaiful; Nugroho, Ary Susatyo; Roshayanti, Fenny (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
This research aims to reveal the profile of students' science learning motivation at MTs Muhammadiyah Al Manar Demak which implements a Pondok Pesantren-based curriculum. Through a qualitative descriptive method with a case study approach, data was collected through a questionnaire which includes three main indicators: students' understanding of the meaning of career (Value of Career), level of motivation to learn science (Science Motivation), and interest in science subjects (Academic Self Concept IPA ). The research results reveal that the majority of students have a deep understanding of the reasons for choosing their career with a percentage of 83%, and their motivation to learn science tends to be high with a percentage of 45.71%, with the majority of students showing good interest in science subjects with a percentage of 57%. These findings provide valuable insight into the factors that influence students' science learning motivation in Islamic boarding school environments. These results can be used as a basis for developing more effective and supportive learning strategies in improving student learning achievement in science, especially in madrasas with Islamic boarding school-based curricula.